2021
DOI: 10.26444/aaem/140076
|View full text |Cite
|
Sign up to set email alerts
|

C-type natriuretic peptide and its contribution to bone growth

Abstract: Kulik-Rechberger B, Trojanowska-Szostek M. C-type natriuretic peptide and its contribution to bone growth. Ann Agric Environ Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…CNP is now regarded as an autocrine/paracrine regulator with broad expression in the body [ 23 ]. CNP produces a series of biological effects by the cGMP signaling pathway through binding to its specific natriuretic peptide receptor B (NPR-B) [ 24 , 25 ], such as regulation of the proliferation of myocardial cells [ 26 ]; maintaining cardiovascular homeostasis [ 27 ]; inhibition of bone growth and cartilage development [ 28 ]; promote follicular development [ 29 ]. Our group’s previous studies have already shown that CNP can induce sperm capacitation in normal people through cGMP [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…CNP is now regarded as an autocrine/paracrine regulator with broad expression in the body [ 23 ]. CNP produces a series of biological effects by the cGMP signaling pathway through binding to its specific natriuretic peptide receptor B (NPR-B) [ 24 , 25 ], such as regulation of the proliferation of myocardial cells [ 26 ]; maintaining cardiovascular homeostasis [ 27 ]; inhibition of bone growth and cartilage development [ 28 ]; promote follicular development [ 29 ]. Our group’s previous studies have already shown that CNP can induce sperm capacitation in normal people through cGMP [ 16 ].…”
Section: Discussionmentioning
confidence: 99%